Forage Diversification of Parent Bali Cattle in Simantri Group 733 Manah Cika Guna Bhakti, Baru Village Tabanan Bali Indonesia - Ni Ketut Mardewi; Candyrine Su Cui Len; Nur Hardy Abu Daud; Luh Suariani; I Nyoman Kaca; Yan Tonga (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
Simantri is agricultural integration activity in Bali, Indonesia covering food crops, horticulture businesses, animal husbandry, fisheries, plantations, and forestry crops in one area/activity location. The Simantri Group 733 Manah Cika Guna Bhakti Desa Baru has been formed since 2009, with available feed sources in the form of grasses that grow naturally (nature grass) and some forage plants such as gamal (Gliricidia sepium) and agricultural crop waste. Forage is the main feed for ruminants, which can be in the form of grasses or fodder plants such as legumes. Partners lack knowledge in the field of feed, especially learning about types of forage that are superior in quantity and quality, and are willing to increase the variety of quality forage sources available throughout the season. Partners also want to get special forage seeds and how to cultivate them. It is necessary to conduct action research for Simantri 733 Manah Cika Guna Bhakti Livestock Farmer Group in Banjar Dinas Baru, Baru Village, Marga District, Tabanan Regency, Bali, to help solve problems faced by partners by providing knowledge about superior types of forage, the introduction of technology and skills in cultivation such as land preparation, seed selection, planting, and care. This international collaboration activity was carried out well and smoothly on October 30, 2021, attended by 20 members of the Simantri group. The method used is the method of extension, active participation of farmers, and exploratory. Based on the evaluation results, the Simantri group has recognized several superior forages and has mastered the technology for the cultivation of superior types of forage. Mastery of technology reaches 80%, so it is necessary to provide further assistance to the group during the first and second cutting and preservation techniques so that the rainforest remains of good quality